Bactericidal activity of the aqueous silver solution on enterobacteral producing extended-spectrum betalactamases - López-Esquen, Fiorella (2024)
Introduction: Silver has been used since ancient times for its significant antibacterial  potential that can be an effective alternative to combat antibiotic-resistant bacteria.. Objective: The objective was to evaluate the bactericidal activity of aqueous silver solution on strains of Escherichia coli and Klebsiella pneumoniae producing extended spectrum beta-lactamases (ESBL). Material and Methods: Experimental study with increasing stimulus, where 225 units of analysis were evaluated, consisting of 14 cultures of E. coli BLEE, 01 culture of Kl. pneumoniae BLEE, 5 concentrations of aqueous solution, with three applications  per experiment. The electrochemical method was used to obtain the aqueous silver solution and its bactericidal activity was determined with the minimum bactericidal concentration.  In addition, the growth curve  of the bacterial strains was established by counting the number of bacterial colonies after exposure to the aqueous silver solution (0, 2, 4, 6, 8 and 24 hours of exposure). Results: The MIC and BMC were  2.5 and 5mg/L  for E. coli and K. pneumoniae BLEE, respectively. The concentrations of 5mg/L and 10mg/L exerted bactericidal activity against the strains evaluated, demonstrating the showing absence of bacterial growth in vitro after 4 and 8 hours of exposure, respectively. Conclusion: The aqueous silver solution presented bactericidal  activity against Escherichia coli and Klebsiella pneumoniae BLEE strains, and it was observed that such activity increased with higher concentration and exposure time.